(In)Visible Boxes: Racialized Intersubjectivity and Transracial Mothering in Senna’s Caucasia - Manuel, Anika (Journal of the Motherhood Initiative for Research and Community Involvement, 2024)
Danzy Senna explores the challenges of racialized intersubjectivity in transracial mothering in her 1998 novel Caucasia. Transracial mothering pertains to mothers who possess a different racial identity from that of their children, most often in mixed-race families. The literature on mixed-race identity and experience is notably limited, particularly concerning motherhood in mixed-race settings. This article addresses this gap and explores racialized intersubjectivity in mother-daughter relationships by analyzing motherhood in Danzy Senna’s novel Caucasia. Racialized intersubjectivity describes how racial differences affect the interchange of thoughts and feelings, both conscious and unconscious, that provide a shared perception of reality between two or more persons. This paper builds upon the literature regarding the effect of race on maternal competence by looking further into racial dynamics in mixed-race families. A careful analysis of the text demonstrates how racial differences between mothers and daughters inherently impact their intersubjectivity, thus complicating their reality.